Characteristics and Safety Profiles of a Hydrocolloid Polyester Dressing Incorporated with Herbal Extract: In Vitro, in Vivo and Randomized Clinical Studies - Namviriyachote N. (2023)
The polyester dressing containing herbal extract had been used for several years. However, some properties had not been investigated. This study examined three parts including in vitro studies, skin irritation in an animal model, and the pilot clinical study in traumatic wounds. In in vitro studies, six different wound dressings consisted of hydrocolloid polyester containing herbal extract (SI-HERB®), hydrofiber (Aquacel®), hydrocolloid polyester (Urgotul®), soft paraffin gauze (Bactigras®), foam (Mepilex®), and biocellulose (Suprasorb® X + PHMB) dressings were comparatively evaluated in physical properties including the fluid absorption, desorption, and fluid drainage ability. The skin irritation test was examined in a rabbit model using SI-HERB® as a tested group. In a clinical study, traumatic patients with leg wounds were randomly assigned to six wound dressings. The primary outcome was the pain level and the secondary outcomes were non-adherence and peri-wound reaction evaluating score. From the study, Bactigras® had the largest pore size but the total area of pore size per field of it was similar to SI-HERB®. There were no significant differences between SI-HERB®, Urgotul®, and Bactigras® in the percentage of absorption and desorption. No dermatologic effect was found in the animal study. In the irritation test on leg wounds, pain level, and peri-wound reaction in hydrocolloid polyester dressing group were significantly lower compared with Aquacel® and Bactigras®. The polyester dressing had the pain level after removal lower than before application while the Mepilex® and Suprasorb® presented that insignificantly increase the pain level. Erythema could be observed in Bactigras®, Aquacel®, and Suprasorb® but the edema scores were not different. A hydrocolloid polyester dressing containing herbal extract had good drainage ability. No skin irritation was reported. Pain scores, removal ability, and peri-wound reaction were also significantly lower with other types of wound dressings. These results suggested that this dressing be an alternative in wound treatment.